Hepatitis B vaccination in preterm infants. Issue 2 (1st September 1997) - Huang, Fu-Yuan; Lee, Ping-Ing; Lee, Chin-Yun; Huang, Li-Min; Chang, Luan-Yin; Liu, Su-Chin
Abstract : AIM: To investigate the immunogenicity and safety of existing recommendations for hepatitis B vaccination in preterm infants. METHODS: Recombinant hepatitis B vaccine (H-B-VAX II, 5 μg per dose) was given to 85 preterm infants divided into two groups, using two different schedules. Forty four group A infants with birthweights of < 2000 g received three doses at 1, 2, and 7 months of age. Forty one group B infants with birthweights of ⩾2000 g received three doses at 0, 1, and 6 months of age. RESULTS: After vaccination, 42 infants from group A (95%) and 37 infants from group B (90%) developed protective levels of antibody. The final seropositive rate and the geometric mean concentration of hepatitis B surface antibody between the two groups were not significantly different. The immune response of preterm infants to hepatitis B vaccines was similar to that of term infants in a previous study. CONCLUSIONS: Preterm infants can be given hepatitis B vaccines using one of the above two different schedules, at a cutoff birthweight of 2000 g.